Thermodynamic measurements and ab initio calculations of the indium-lithium system - Dębski A.; Gierlotka W.; Zabrocki M.; Góral A.; Gąsior W. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The limiting enthalpy of the solution of liquid indium in liquid tin was measured at 723 K. The calorimetric method was applied to determine the standard enthalpy of the formation of intermetallic phases and alloys from the In-Li system. The measurements were done at 747 K and 756 K. The structures of prepared alloys were confirmed by the X-ray diffraction measurements. Besides that, the ab initio calculations allowed the modeling of the formation energies, the volume thermal expansion, the heat capacity under constant pressure, and the elastic properties of the intermetallic phases. The theoretical formation energies show good agreement with the experimental findings. The analysis of the phonon dispersion indicates an instability of the InLi phase in the Fd-3m space group. A further investigation on the atomic arrangement in the case of the equiatomic ratio is suggested.